Nature Tourism, Conservation, and Development in KwaZulu Natal, South Africa. - Lutz, Ernst; Aylward, Bruce A. (World Bank e-Library., 2003)
This volume assesses how various institutional, policy and managerial options can enhance nature tourism's contribution to the "triple bottom line". There are win-win outcomes but also trade offs between various policy objectives including: economic growth; poverty reduction; conservation finance/biodiversity conservation. This collaborative report highlights the complementarities and the trade-offs in promoting and managing sustainable nature tourism development and conservation.; Nature tourism is important for many developing countries, including South Africa. If wisely managed, nature tourism offers valuable opportunities for generating revenues for development and for conservation. The recommendations are fairly specific to the Ezemvelo KwaZulu Natal Wildlife area. By combining various options into an integrated package to achieve economic development, equity and conservation, such a balanced approach provides pro-poor tourism opportunities for local communities, by reinvesting the proceeds in on-the-ground work in the reserves and in the community. It requires collaboration with private game reserves to drop fences and could contribute to a successful transformation of wildlife management to a nature tourism economy.